PENGARUH LEVERAGE, PROFITABILITAS, LIKUIDITAS, SALES GROWTH DAN FIRM SIZE TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PULP & KERTAS DAN PLASTIK & KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Panji Satrio Aji; Saiful Anwar (LP2M Universitas Bina Bangsa, 2022)
The purpose of this research is to find out the influence of leverage, profitability, liquidity, sales growth and firm size on financial distress. This research uses this type of quantitative research using multiple linear regression analysis. This study uses secondary data in the form of panel data on Pulp &Paper and Plastic &Packaging companies available on the Indonesia Stock Exchange (IDX) for the period 2016-2020. The data management used is Eviews 9. The sampling method used is purposive sampling that uses several criteria so that there are 7 companies that are sampled research. Based on the results of the test, it was found that partially the leverage variable has no significant effect on financial distress, profitability has a positive effect on financial distress, negative liquidity effect is not significant to financial distress, sales growth has a positive effect not significant on financial distress, firm size has a significant positive effect on financial distress. Simultaneously the variables of leverage, profitability, liikuidity, sales growth and firm size have a significant effect on financial distress